Predictors of Psychological Distress among Old Aged - B. J., Kavery; K., Manikandan (Innovare Journal of Education, 2022)
Psychological distress is linked with the lack of social support and loneliness. The Elderly is suffering from many psychological issues and a lack of social support. Often, in old age homes, the lack of immediate friends and family leads them to many issues like loneliness, which affects their mental health. So it is essential to address this issue to provide care and support them. This study aimed to understand the contributing factors of psychological distress and influencing factors of psychological distress, loneliness, religiosity, and social support. The study was conducted on 159 older people (age range 60-90 years) of Thrissur and its neighboring places by employing a convenient sampling technique. The psychological distress scale was used to measure psychological distress The UCLA Loneliness Scale, Perceived Social Support Scale, and Religiosity Scale were used to measure loneliness, perceived social support, and religiosity, respectively. Personal details of the participants, such as age, sex, socio-economic status, marital status, etc., were collected using a personal data sheet. Results revealed that the loneliness and support from the family were highly contributing to predictors of psychological distress, and loneliness and support from friends contributed to depression. Males and females differ on psychological distress and its components, namely anxiety and depression. Moreover, males and females experienced similar religiosity and stress levels, and females experienced higher levels of loneliness than males. As a result of lower support from family, friends, and special person and overall perceived social support, there occurs a higher level of depression. Psychological distress will be high when there is lower social support from family, friends, and special people. Also, when there is greater psychological distress, there will be high loneliness. Older persons will have high religiosity when there is high loneliness. Stress and depression differ between people living in old age homes and Pakal Veedu. Reduction in loneliness occurs when there is a presence of a special person in their life.